Knowledge Levels and Perceived Effect of Ecosystem Services and Valuation on Extension Delivery in North West Province, South America - O.I. Oladele (Journal of International Agricultural and Extension Education, 2012)
A simple random sampling technique was used to select 100 extension officers in North West Province, South Africa. Data on knowledge levels and perceived effect of ecosystem services and valuation on extension deliverywere collected and analyzed using percentages. The results show that a wide range of knowledge levels exists on ecosystem services and valuationissues and that extension services should change from a generalist approach to a specialist approach; “extension messages should incorporate ecosystems service information”; extension agents would benefit from “increase[s] in extension research skill” and “use of multimedia strategy”; users require new skills; “extension officers need...new training” and “extension messages should address vulnerability of ecosystem services” in response to ecosystem services and valuation issues. The results have several implications for training and educating extension officers in the areas of ecosystem services used for tourism, hedonic pricing, and governance of ecosystem services.
Keywords: Ecosystem Services; Extension Delivery; Extension Officers; North West Province; South America; Knowledge; Valuation